Explaining civil war a rational choice approach - Murshed, Syed Mansoob; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2010)
This book explores the pre-conditions for conflict in terms of growth failure and critically appraises the greed and grievance theories common to conflict literature. It is argued that various institutional mechanisms of restraint that can be labeled the 'social contract' are crucial for violent conflict avoidance. The reasons underpinning the instability of treaties ending civil wars, post-conflict reconstruction issues, liberal peace theory, and how globalization and conflict relate are also examined.
1. Introduction -- 2. Growth and conflict -- 3. Greed and grievance -- 4. The uneasy commitment to peace -- 5. The social contract and lasting peace -- 6. Post-war economic reconstruction -- 7. The liberal peace and globalization -- 8. Conclusions.
Includes bibliographical references and index.
Keywords: Civil war; Peace-building.; Electronic books